Application of Metabolomics to Identify Hepatic Biomarkers of Foie Gras Qualities in Duck - Mozduri, Zohre; Lo, Bara; Marty-Gasset, Nathalie; Masoudi, Ali Akbar; Arroyo, Julien; Morisson, Mireille; Canlet, Cécile; Bonnet, Agnès; Bonnefont, Cécile M. D. (Frontiers in Physiology, 2021)
The foie gras is a traditional dish in France that contains 50 to 60 % of lipids. The high fat content of liver improves the organoleptic qualities of foie gras, but also reduces its technological yield at cooking (TY). As the valorization of the liver as foie gras products is strongly influenced by the TY, classifying the foie gras in function of their potential technological quality before cooking them is a main challenge for producers. Therefore, the current study aimed to identify hepatic biomarkers of foie gras qualities like liver weight (LW) and TY. A group of 120 male mule ducks were reared and overfed during 6 to 12 days and their livers were sampled and analyzed by proton nuclear magnetic resonance (1H-NMR). Eighteen biomarkers of foie gras qualities were identified, nine for both LW and TY, five specific to LW and four specific to TY. All biomarkers were strongly negatively correlated to the liver weights and positively correlated to the technological yield, except for the lactate and the threonine, and also for the creatine that was negatively correlated to foie gras technological quality. As a result, in heavy livers the liver metabolism was oriented through a reduction of carbohydrate and amino acid metabolisms and the plasma membrane could be damaged which may explain the low technological yield of these livers. The detected biomarkers have been strongly discussed with the metabolism of liver in non alcoholic steato hepatitis.